2022
DOI: 10.1021/acsami.2c06449
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of the Thermodynamics of Integer Charge Transfer vs Charge-Transfer Complex Formation in Doped Conjugated Polymers

Abstract: Molecular dopants such as 2,3,5,6-tetrafluoro-7,7,8,8-tetracyanoquinodimethane (F4TCNQ) can interact with conjugated polymers such as poly­(3-hexylthiophene-2,5-diyl) (P3HT) in two different ways: they can undergo integer charge transfer (ICT) or they can form a partial-charge-transfer complex (CTC). Both are seen experimentally, but the CTC has been challenging to characterize, making it difficult to answer questions such as the following. Which polymorph is more stable? Do they have similar barriers for form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 66 publications
1
33
0
Order By: Relevance
“…They concluded that there exists, indeed, a kinetically unstable, crystalline CPX polymorph, as found by Jacobs et al in addition to a stable CPX phase in the amorphous regions. These findings were followed up by Wu et al [23] employing all-atom molecular dynamics simulations which demonstrated that the IPA and CPX crystalline phases in this system are respectively entropy-and enthalpy-driven. There, however, the key mechanism favoring IPA formation was suggested to be a nucleation process starting with as few as 2-3 dopant radical anions as critical nucleus among the simulated 1728 P3HT monomer units while, in contrast, no critical nucleus was found for the crystalline CPX phase up to the maximum dopant loading that was investigated (144 CPX-forming dopants).…”
Section: Introductionmentioning
confidence: 78%
See 4 more Smart Citations
“…They concluded that there exists, indeed, a kinetically unstable, crystalline CPX polymorph, as found by Jacobs et al in addition to a stable CPX phase in the amorphous regions. These findings were followed up by Wu et al [23] employing all-atom molecular dynamics simulations which demonstrated that the IPA and CPX crystalline phases in this system are respectively entropy-and enthalpy-driven. There, however, the key mechanism favoring IPA formation was suggested to be a nucleation process starting with as few as 2-3 dopant radical anions as critical nucleus among the simulated 1728 P3HT monomer units while, in contrast, no critical nucleus was found for the crystalline CPX phase up to the maximum dopant loading that was investigated (144 CPX-forming dopants).…”
Section: Introductionmentioning
confidence: 78%
“…In the following, we discuss the nucleation effect for IPA formation, postulated by Wu et al [23], as a potential way to explain the differences between the doping phenomenology of FTCNQ and TCNQ. When assigning a host HOMO-DOS width σ to the nucleation threshold-concentration χ IPA ≈ 0.1% of ionized dopants for each total dopant molar ratio χ, we observe less broadening for higher χ, suggesting a higher probability for the occurrence of the crystalline IPA phase, all while our experimental data shows increased CPX formation.…”
Section: Drivers Of Ipa Formation-ftcnq Versus Tcnqmentioning
confidence: 99%
See 3 more Smart Citations